Making Strides Towards Space Security in Low Earth Orbit - Cesari, Laetitia (Global Governance of Low Earth Orbit Satellites, 2025)
This chapter addresses the emerging domain of space security as it pertains to the governance of LEO satellites. It outlines current international legal instruments and soft law norms, critically assessing their adequacy in responding to the dual-use nature of LEO systems. The chapter also emphasizes the need for inclusive multilateral dialogues to safeguard the peaceful use of outer space.